Foot Massage dan Latihan Range of Motion Dapat Mengatasi Gangguan Mobilitas Fisik pada Lansia dengan Stroke - Dohanis, Putri; Rantesigi, Nirva (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Introduction: the elderly are part of the growth process. One of the problems that often occur in the elderly with stroke cases is a decrease in physical mobility. This can be overcome by nursing interventions providing food massage and range of motion exercises. Method: with a case study approach. The research sample was one post-stroke patient who experienced a decrease in muscle strength. by giving foot massage and ROM exercises for 15-30 minutes 2 times a day in the morning and evening for 6 days. Results: there were complaints, weakness in the right extremity, selurred speech, difficulty walking asymmetrical mouth. Nursing interventions identify physical tolerance for movemen. Monitor blood pressure before starting mobilization and ambulation. Implementation facilitates changing positions as comfortable as posibble, providing foot massage and range of montion exercises. Evaluation TTV: 120/90 mmHg, N: 90x/minutes, R: 22x/minutes, S:36.0ᵒC efter being given foot massage and range of montion exercises whit a duration of 15-3o minutes 2 tamies a day in the morning dan evening for 6 days showed that the client eperianced an increase in muscle strength from a score of 2 to 3. Conclusion: giving food massage and range of motion can increase muscle strength. It is hoped that nurses can provide this intervention as a companion to non-pharmacological therapy to overcome physical problems in patients with stroke